Health Related Experiences of Maritime Students During their On-Board Training on Inter-Island Vessels - Alday, Cecille L.; Paet, Rose Ann R. (Proceedings Series on Health & Medical Sciences, 2025)
Maritime students face unique health challenges during their rigorous training programs, particularly during the mandatory on-board training. This study investigates the health-related experiences of maritime students, focusing on physical, psychological, and social factors impacting their well-being. A descriptive-phenomenological approach was used to explore the health challenges faced by five maritime students from Midway Colleges Inc. during their first three months of on-board training. Data were collected through semi-structured interviews conducted over two months, from June to July 2023, examining their health experiences, adaptation strategies, and available health services. Participants reported several health issues, including hypertension, sexually transmitted diseases, and musculoskeletal disorders. Environmental factors like vibration, noise, and climate change, along with unhealthy lifestyles, contributed to these problems. Students used coping strategies, such as maintaining healthy lifestyles and seeking psychological support. Health services on-board were crucial but insufficient, prompting a call for improved health support. Maritime students encounter significant health challenges during their on-board training, which are exacerbated by environmental and lifestyle factors. Adaptation strategies and support systems play a critical role in managing these challenges. There is a pressing need for educational institutions and health workers to enhance health education, resilience training, and health services, ensuring better support for maritime students during their training. This will help prepare them for the demands of their profession and improve their long-term health outcomes.